PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) PADA PEMBELAJARAN MENULIS TEKS CERITA PENDEK KELAS IX SMPN 2 PADALARANG - Kania, Sinta; Wikanengsih; Suhara, Alfa Mitri (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research is motivated by the students' minimal skills in expressing ideas into written form, namely short story texts. The application of a learning model that is not suitable for the learning material requires an appropriate learning model to be applied, especially in the final activities that produce products. Therefore, researchers recommend implementing an appropriate and effective learning model, namely the project based learning model in learning short story texts. The population in this study was 22 students. The method used to analyze this research is the quantitative method. The aim of this research is to determine the learning outcomes of students using the project based learning model in class IX at SMPN 2 Padalarang. The instrument used in this research is a test instrument. The data collected in this research was obtained through pretest and posttest results in learning to write short story texts using the project based learning model. Based on the test results, there was an increase in learning outcomes from the pretest and posttest with average scores of 42 and 86. The conclusion of this research is that the application of the project based learning model in short story learning succeeded in improving the writing skills of class IX students at SMPN 2 Padalarang.